Seafood simple - Ripert, Eric (Random House, 2023)
"In its three decades at the top of New York City's restaurant scene, Le Bernardin has been celebrated as one of the finest seafood restaurants in the world and its iconic chef Eric Ripert as the expert in fish cookery. Now, in Seafood Simple, Ripert demystifies his signature cuisine, making it accessible to home cooks of all skill levels-yet still with elegance and panache. Breaking down cooking techniques in a step-by-step process along with accompanying images, this book teaches readers how to master core skills, from poaching and deep frying to filleting a fish and shucking an oyster. These techniques are then applied to 85 straightforward, delicious recipes. Dishes like Tuna Carpaccio, Crispy Fish Tacos, Shrimp Tempura, Miso Cod, and Spaghetti Vongole show us how to bring out the vibrant flavor and incredible versatility of seafood. Each recipe is complete with a gorgeous image by renowned photographer Nigel Parry, as well as step-by-step photos for each of the twenty techniques taught in the book"--